Graceling - Cashore, Kristin (Cashore, Kristin. Graceling Realm book., 2008)
In a world where some people are born with extreme and often-feared skills called Graces, Katsa struggles for redemption from her own horrifying Grace, the Grace of killing, and teams up with another young fighter to save their land from a corrupt king.